FLUCTUATION OF WATER QUALITY IN SOME COASTAL AREAS IN VIETNAM - Nghi, Duong Thanh (Vietnam Journal of Marine Science and Technology, 2018)
Water quality was assessed in the dry season (in April 2014) and the rainy season (in August 2013) in some coastal areas: Bach Dang river mouth, Da Nang bay and Thi Nai pond. The results showed that the seasonal fluctuation was different from each area. According to the national technical regulation for coastal water quality (QCVN 10MT: 2015/BTNMT), some environment parameters were over the limited values. The average of water column temperature in the dry season was in the range from 30.18 - 30.45oC (>30oC) at Thi Nai pond; the average of the total suspended solid (TSS) concentration in water column was from 59.8 mg/l to 81.6 mg/l (>50 mg/l) at Bach Dang river mouth; the average of chemical oxygen demand (COD) concentration in water column was in the range from 5.78 - 8.20 mg/l (> 3 mg/l) at Thi Nai pond; the average of ammonium (NH4+) concentration in water column was from 119.1 mg/l to 144.7 mg/l (>100 mg/l) at Bach Dang river mouth; the average of copper (Cu) concentration in water column was in the range from 30.9 - 51.5 µg/l (>30 µg/l) at Thi Nai pond; the arsenic (As) concentration in water at Bach Dang river mouth, Da Nang bay, Thi Nai pond was 12.52 - 14.26 µg/l; 23.08 - 30.30 µg/l; 6.80 - 20.00 µg/l respectively (>10 µg/l); The residue concentration of DDT group was in low range, but DDD and DDE concentrations were over limitation ( > 4 ng/l) at all three areas. So, the water quality not only seasonally fluctuated but also in was at risk of pollution by many different environmental parameters.